2008
DOI: 10.1002/bit.21825
|View full text |Cite
|
Sign up to set email alerts
|

Fungal removal of gaseous hexane in biofilters packed with poly(ethylene carbonate) pine sawdust or peat composites

Abstract: The removal of volatile organic compounds (VOC) in biofilters packed with organic filter beds, such as peat moss (PM) and pine sawdust (PS), frequently presents drawbacks associated to the collapse of internal structures affecting the long-term operation. Poly(ethylene ether carbonate) (PEEC) groups grafted to these organic carriers cross linked with 4,4'-methylenebis(phenylisocyanate) (MDI) permitted fiber aggregation into specific shapes and with excellent hexane sorption performance. Modified peat moss (IPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…This was similar to the results of Arriaga and Revah (2005), who reported 59% mineralization of hexane in a microcosm experiment using a bacterial consortium. Hernández-Meléndez et al (2008) also reported that 50% of the inlet hexane was completely transformed into CO 2 in a hexane removal biofilter system. The lack of non-14 CO 2 in the air phase indicated that all of the intermediates were nonvolatile, and the lower proportion of metabolites in the EH831 culture suggests they were more quickly degraded or taken up than by the consortium culture.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This was similar to the results of Arriaga and Revah (2005), who reported 59% mineralization of hexane in a microcosm experiment using a bacterial consortium. Hernández-Meléndez et al (2008) also reported that 50% of the inlet hexane was completely transformed into CO 2 in a hexane removal biofilter system. The lack of non-14 CO 2 in the air phase indicated that all of the intermediates were nonvolatile, and the lower proportion of metabolites in the EH831 culture suggests they were more quickly degraded or taken up than by the consortium culture.…”
Section: Discussionmentioning
confidence: 94%
“…Because of its lower solubility, hexane is degraded relatively slowly by bacteria compared with benzene, toluene, and methyl ethyl ketone probably due to its slow transfer from the gaseous to the liquid phase Hernández-Meléndez et al 2008). Therefore, to improve the degradation of hexane, surfactants have been added to the aqueous phase (Kastner et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many processes were tested for addressing the bioavailability of hydrophobic contaminants. One is the introduction of surfactants (Aly Hassan and Sorial, 2008;Woertz and Kinney, 2004), providing favorable conditions for fungi (Aly Hassan and Sorial, 2008;Arriaga and Revah, 2005a;Hernández-Meléndez et al, 2008;Spigno and De Faveri, 2005;Van Groenestijn et al, 2001); others include mixture of n-hexane with other less hydrophobic compound such as benzene (Aly Hassan and Sorial, 2010a), introduction of more hydrophilic contaminants in mixture with n-hexane, such methanol (Zehraoui et al, 2012(Zehraoui et al, , 2013, and most recently the alternate use of methanol with n-hexane (Zehraoui et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Current literature shows a very great interest in using molecular biology techniques for microbial species identification from environmental samples (García-Peña et al, 2008;Vigueras et al, 2009). Most reported species for n-hexane biodegradation were Fusarium solani (Arriaga and Revah, 2005b;Hernández-Meléndez et al, 2008), Rhinocladiella similis (Vigueras et al, 2009), and Aspergillus niger (Spigno et al, 2003). Combination of Fusarium solani, Aspergillus niger, and Dothioraceae.…”
mentioning
confidence: 99%